Circuit design for single-order system with fractional power using singularity function approach / Fauziah Abd Yakin - Abd Yakin, Fauziah (1995)
This project presents the analysis and synthesis of single-order system with fractional power m. The singularity function method and the partial-fraction expansion for a rational function to approximate the function by a series of negative real pole-zero pairs was used. First, the analysis is done for 0<ml. Singularity function method is used to approximate the fractional-order function by pole-zero pairs. The function is then synthesized to circuit form. A circuit design method for the synthesis is proposed and the resulted circuit is simulated using PSPICE. The simulation results are presented for both the frequency and unit-step responses and compared with the responses from the original transfer function plotted using MATHCAD. In the synthesis, the magnitude of the presented transfer function is approximated. The passive filter design and active filter design method are proposed in this thesis.